2004
DOI: 10.1007/s00442-004-1573-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of lifetime reproductive success in three species of European ducks

Abstract: Number of breeding attempts is a strong correlate of lifetime reproductive success (LRS) in birds, but the relative importance of potentially interacting factors affecting LRS has rarely been fully evaluated. We considered simultaneously five main factors hypothesized to influence LRS (age at first breeding, nesting date, number of breeding attempts, female traits, brood parasitism) by analyzing with path analysis 22-year data sets for 1,279 individually marked females and their offspring in tufted duck ( Ayth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 27 publications
9
40
1
1
Order By: Relevance
“…These individuals may also cope better with the costs of reproduction, and may attain higher success regardless of their lifespans. This explanation may be more consistent with our results than improving experience, as a large number of individuals produce no returning young despite breeding several times during their lives (also see Gustafsson 1989;Blums and Clark 2004). Females of many species apparently prefer older males (Enstrom 1993;Richardson and Burke 1999), or traits that indicate the expected lifespan of males (Jennions et al 2001), thereby often enhancing the quality of young they produce (Saetre et al 1995;Hegyi et al 2006b).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These individuals may also cope better with the costs of reproduction, and may attain higher success regardless of their lifespans. This explanation may be more consistent with our results than improving experience, as a large number of individuals produce no returning young despite breeding several times during their lives (also see Gustafsson 1989;Blums and Clark 2004). Females of many species apparently prefer older males (Enstrom 1993;Richardson and Burke 1999), or traits that indicate the expected lifespan of males (Jennions et al 2001), thereby often enhancing the quality of young they produce (Saetre et al 1995;Hegyi et al 2006b).…”
Section: Discussionsupporting
confidence: 81%
“…There are two main determinants of the number of lifetime recruits: lifespan and the number of recruits per breeding attempt. Several studies have identified longevity or the number of breeding attempts as an important determinant of LRS (birds : Gustafsson 1986;Merilä and Sheldon 2000;Blums and Clark 2004;mammals: Clutton-Brock 1988;Bérubé et al 1999). However, a prolonged lifespan in itself is not sufficient to be successful, as a considerable number of individuals do not produce any recruits despite their long reproductive lives (Gustafsson 1989;Blums and Clark 2004), and even individuals that do produce recruits vary greatly in productivity (Newton 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ducks (Anatidae) are among the species for which survival and breeding success have been shown to increase with body condition (Alisauskas and Ankney 1992;Blums and Clark 2004), but repeated body condition assessments of the same individuals through time have, again, mostly been performed on breeding birds, generally only females (e.g. Hepp and Kennamer 1993;Milonoff et al 2002;Blums et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that examine the relationship between LRS and morphology are also common (Bryant 1989, Mills 1989, Krüger 2002, Blums and Clark 2004, MacColl and Hatchwell 2004. For instance, Jensen et al (2004) studied LRS of House Sparrows (Passer domesticus) and found that morphological traits, like badge size and bill length, explained a significant proportion of variation in male LRS.…”
Section: Studies Of Lrs Are Particularly Valuable When Patterns Of Vamentioning
confidence: 99%